Magazine journalism - Holmes, Tim; Nice, Liz (Journalism studies: key texts, 2012)
A much needed digest of magazine journalism that analyses the origins of this global format with a view to understanding the future directions of the magazine model. It takes an economic and policy focused stance to provide a comprehensive analysis of not just the magazine, but the magazine industry